Fine-scale genetic structure of the overwintering Chilo suppressalis in the typical bivoltine areas of northern China - Zhu, Ke-Xin; Jiang, Shan; Han, Lei; Wang, Ming-Ming; Wang, Xing-Ya (PloS one, 2020)
The rice stem borer (RSB), Chilo suppressalis (Lepidoptera: Pyralidae), is an important agricultural pest that has caused serious economic losses in the major rice-producing areas of China. To effectively control this pest, we investigated the genetic diversity, genetic differentiation and genetic structure of 16 overwintering populations in the typical bivoltine areas of northern China based on 12 nuclear microsatellite loci. Moderate levels of genetic diversity and genetic differentiation among the studied populations were detected. Neighbour-joining dendrograms, Bayesian clustering and principal coordinate analysis (PCoA) consistently divided these populations into three genetic clades: western, eastern and northern/central. Isolation by distance (IBD) and spatial autocorrelation analyses demonstrated no correlation between genetic distance and geographic distance. Bottleneck analysis illustrated that RSB populations had not undergone severe bottleneck effects in these regions. Accordingly, our results provide new insights into the genetic relationships of overwintering RSB populations and thus contribute to developing effective management strategies for this pest.